Zieve's Syndrome Presenting With Severe Hypertriglyceridemia. Issue 7 (July 2019) - Choudhry, Faiza; Kathawa, Jolian; Kerton, Kelsey; Farshadsefat, Seina; Piper, Marc
Abstract : ABSTRACT: Zieve's syndrome (ZS) is a rare disease characterized by a triad of hemolytic anemia, cholestatic jaundice, and transient hyperlipidemia seen in patients with alcoholic steatohepatitis. We report a case of ZS with severe hypertriglyceridemia. Among the reported cases of ZS in English literature, we believe this is the first case of the syndrome presenting with severe hypertriglyceridemia requiring plasmapheresis.